MELAWAN STIGMA : TREN LAJANG PADA PEREMPUAN BERKARIR MELANGGAR NORMA SOSIAL: ANALISIS BIBLIOMETRIK - PRISCINDY NAZRANI WILA (LPPM Universitas Negeri Surabaya, 2025)
Trend for being single women with active careers is increasingly nowadays. Wanting to focus on developing a career is one of the reasons women choose to put off marriage. choosing career towards marriage is not so accaptable in society. The times don’t necessarily change the people’s mindsets who are closely related to patriarchal culture for women. The aim of this research is to find the literature development contains about the society’s stigma towards career women who choose to be single in this era. The research method was bibliometric analysis methods, used Vosviewer software to see the development and relationship between the society’s stigma towards single women who choose careers. The research results through Vosviewer visualisation, show that stigma and society's perspectives on women are still a matter of discussion today. This relatable to women inequality gender, especially for single women who actively developing career. The research conclusions was indicated a change in women perspective toward the marriage, that makes single women able to face the society’s stigma by avoiding and overlooking the stigmas of these people and preferring to focus on their career to achieve economic independence and mental readiness before marriage. Keywords: Stigma, Single, Career Woman, Social Norms.